Comparative Study Between Radiological and Surgical Findings of Chronic Otitis Media - Prata, Anelise Abrahao Salge; Antunes, Marcos Luiz; de Abreu, Carlos Eduardo Cesario; Frazatto, Ricardo; Lima, Bruno Thieme (Arquivos Internacionais de Otorrinolaringologia, 2011)
Introduction: The chronic otitis media (COM) is a prevalent disease and the most frequent cause of indication to mastoidectomy. Many studies have evaluated the use of tomography (CT) of temporal bones for preoperative evaluation of COM and its indication in the preoperative approach is still controversial nowadays.Objective: To evaluate the sensitivity of the clinical and radiological findings of COM according to the intraoperative surgical results and histopathological findings.Method: Transversal retrospective study through collection of record data of patients with COM submitted to mastoidectomy in the period from 2007 through 2008 in our service.Results: From a total of 82 ears, 40.24% had cholesteatoma. The CT presented 72.73% of sensitivity in the identification of cholesteatoma, 56.67% in the identification of changes to the ossicular chain and 100% in that of erosion of the lateral semicircular canal.Conclusion: The clinical and radiological findings showed a high level sensitivity with intraoperative findings as regards to the presence of cholesteatoma, large changes of the ossicular chain and erosion of the lateral semicircular canal. For minor changes to the ossicular chain, the facial nerve canal and the tympanic tegmen they described low sensitivity.
Keywords: tomography; temporal bone; suppurative otitis media; cholesteatoma